BENTUK PERSUASIF PADA UNGGAHAN KONTEN AKUN YOUTUBE JESS NO LIMIT DAN IMPLIKASINYA PADA PEMBELAJARAN BAHASA INDONESIA DI SMP - Muhammad Thoif; Afsun Aulia Nirmala; Syamsul Anwar (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this study is to examine the persuasive form contained in the content of Jess No Limit Youtube Account, describing the persuasive form included in the video uploaded by Jess No Limit Youtube Account, and describing its implications for the Indonesian language learning for junior high school students. This study uses Searle's theory in Hermaji (2016) and is supported by other theories. The data in this study in the form of persuasive forms obtained from speech pieces expressed by jess no limit; this study uses a descriptive approach with observation techniques and continued by using the recording technique after the data is obtained then the data will be analyzed by using descriptive analysis techniques in which there are various steps to analyze this data. The results of this persuasive form of research contain 100% percentage data with data collected as much as 55 data with the following details: 19 data with a percentage of 35% persuasive speech in affirmative or representative speech, there are also 7 data with a percentage of 12% persuasive speech in the act of commissioning speech, then there is also 21 data with a percentage of 39% about persuasive speech in an expressive speech act,  In addition, there are 4 data with a percentage of 7% about persuasive speech in a directive speech act. Lastly, there are 4 data with a percentage of 7% persuasive speech in declarative speech. As a suggestion from researchers, it would be better for this study to be more in-depth and more focused on one specific study object of the five types of persuasive forms that have been in this study.Keywords: Pragmatics, Persuasive, Youtube